Differences In The Implementation of Good Corporate Governance In Conventional Banks and Sharia Banks In Indonesia - Angrum Pratiwi; Slamet Haryono (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
This type of research is content analysis, namely analyzing various regulations and reports that have been published. The research sample consists of three Conventional Banks and three Islamic Banks. The results show that Conventional Banks and Islamic Banks have both complied with the law, Bank Indonesia regulations, OJK regulations. However, they have some differences regarding religious foundations in implementing GCG in Islamic Banks. The Sharia Supervisory Board (DPS) is only owned by Islamic Banks, as a company supervisor to remain sharia compliant. GCG external assessment must be carried out immediately by Islamic Banks, aiming to increase competition a conventional institutions in the Islamic financial industry.